Photoprotection mechanisms under different CO2 regimes during photosynthesis in a green alga Chlorella variabilis - Ueno, Yoshifumi; Shimakawa, Ginga; Aikawa, Shimpei; Miyake, Chikahiro; Akimoto, Seiji (Photosynthesis research, 2020)
Oxygenic photosynthesis converts light energy into chemical energy via electron transport and assimilates CO 2 in the Calvin–Benson cycle with the chemical energy. Thus, high light and low CO 2 conditions induce the accumulation of electrons in the photosynthetic electron transport system, resulting in the formation of reactive oxygen species. To prevent the accumulation of electrons, oxygenic photosynthetic organisms have developed photoprotection mechanisms, including non-photochemical quenching (NPQ) and alternative electron flow (AEF). There are diverse molecular mechanisms underlying NPQ and AEF, and the corresponding molecular actors have been identified and characterized using a model green alga Chlamydomonas reinhardtii . In contrast, detailed information about the photoprotection mechanisms is lacking for other green algal species. In the current study, we examined the photoprotection mechanisms responsive to CO 2 in the green alga Chlorella variabilis by combining the analyses of pulse-amplitude-modulated fluorescence, O 2 evolution, and the steady-state and time-resolved fluorescence spectra. Under the CO 2 -limited condition, ΔpH-dependent NPQ occurred in photosystems I and II. Moreover, O 2 -dependent AEF was also induced. Under the CO 2 -limited condition with carbon supplementation, NPQ was relaxed and light-harvesting chlorophyll-protein complex II was isolated from both photosystems. In C. variabilis , the O 2 -dependent AEF and the mechanisms that instantly convert the light-harvesting functions of both photosystems may be important for maintaining efficient photosynthetic activities under various CO 2 conditions.